CIVIL ENGINEERING, SCIENCE AND TECHNOLOGY CHALLENGES: GEOTECHNICAL AND GEOENVIRONMENTAL ENGINEERING - Wan Hashim, Wan Ibrahim (UNIMAS Publisher, 2022)
The book is based on scientific and technological advances in various Geotechnical and Geoenvironmental Engineering areas of Civil Engineering. It nurtures therefore the exchange of discoveries among research workforces worldwide including those focusing on the vast variety of facets of the fundamentals and applications within the Geotechnical and Geoenvironmental Engineering area. To offer novel and rapid developments, this book contains original contributions covering theoretical, physical experimental, and/or field works that incite and promote new understandings while elevating advancement in the Geotechnical and Geoenvironmental Engineering fields. Works in closing the gap between the theories and applications, which are beneficial to both academicians and practicing engineers, are particularly of interest to this book that paves the intellectual route to navigate new areas and frontiers of scholarly studies in Geotechnical and Geoenvironmental Engineering area.